Functionalizing building envelopes for greening and solar energy: Between theory and the practice in Egypt - Marzouk, Mai A.; Salheen, Mohamed A.; Fischer, Leonie K. (Frontiers in Environmental Science, 2022)
The building sector is one of the most resource-intensive industries. In Egypt, buildings consume 60% of electricity, produce 8% of CO2 emissions, and anthropize agricultural land, peri-urban and urban landscapes. To compensate for these consumption patterns, building envelopes can become productive in terms of greening and energy production. This encompasses the implementation of productive building systems that include (a) greening systems such as building-integrated vegetation and agriculture systems and (b) solar energy systems such as building-applied and integrated photovoltaics. For Egypt, the transformation towards more productive buildings still lacks a holistic understanding of their status and implementation requirements. This paper undergoes a comprehensive analysis of the two systems’ classifications, benefits, challenges, and implementation aspects based on a thorough assessment of 121 studies and 20 reports addressing them. This is coupled with a contextual analysis using questionnaires (n=35) and semi-structured interviews (n=13) with Egyptian experts and suppliers. Results showed that a large variety of systems is studied in literature and exists in the local market. Among the most purchased productive building systems in the Egyptian market, according to experts, are hydroponics, planter boxes/pots, roof-mounted photovoltaic panels, and solar water heaters. The main benefits of greening and solar energy systems are identified as enjoying the greenery view and reducing energy expenses, respectively. On the other hand, the high initial cost was considered the main barrier for both systems. Results also identified multiple commonalities between the two systems in terms of spatial and environmental applicability aspects (e.g., accessibility and safety, net useable area, sun exposure, and wind exposure) as well as environmental performance aspects (e.g., energy demand and emissions reduction, heat flow reduction). For future research, we highlight the importance of analyzing integrated solutions that make use of the identified synergies between systems and maximize production potentials.